'Authoritarian neoliberalism' and the Australian border-industrial complex. (April 2019) - Smith, Cameron
What functions do the securitization and the militarization of the border serve under 'authoritarian neoliberalism' in Australia? Having pursued the policy of mandatory detention of all undocumented migrants since 1992, the Australian government has also increasingly sought to outsource, privatize, and offshore the construction and operation of its immigration detention facilities, whilst simultaneously engaging in increasingly authoritarian interventions via the militarization of border control. This article seeks to problematize these developments by constructing an emergent cartography of the various links between the ongoing processes of neoliberal structural adjustment, and the intensification of the policing and punitive apparatuses of the Australian border-industrial complex. Accordingly, using theoretical insights gleaned from emergent work on 'authoritarian neoliberalism' and from race critical theory as a cue, I outline in this article three functions of the border within punitive approaches to immigration control under neoliberal structural adjustment in Australia: first, as an apparatus of ongoing colonial power; second, as a technology of racial differentiation through its functioning as a 'filter' that privileges certain migrant bodies over others, and as an 'insulator' against popular dissent; third, as a site of profit and accumulation for transnational capital.